Effects of Standardized Ileal Digestible Threonine to Lysine Ratio on Finishing Pig Growth Performance - Rafe Q. Royall; Hilario M. Cordoba; Robert D. Goodband; Mike D. Tokach; Joel M. DeRouchey; Jordan T. Gebhardt; Jason C. Woodworth (Kansas Agricultural Experiment Station Research Reports, 2024)
The objective of these experiments was to evaluate the effect of varying SID Thr:Lys ratios on growth performance of growing and finishing pigs. In each experiment, pens of pigs were blocked by BW and barn, and randomly assigned to one of six dietary treatments in a randomized complete block design with nine or 10 pigs per pen and 11 or 12 replications per treatment. A similar number of barrows and gilts were placed in each pen. In exp. 1, 684 pigs (DNA 600 × 241: initially 82.5 ± 2.99 lb) were used in two separate studies, lasting 35 and 28 d, respectively. In exp. 2, 662 pigs (600 × 241, DNA; initially 212.1 ± 2.29 lb) were used in two separate 28-d studies. Dietary treatments were corn-soybean meal-based and formulated with increasing SID Thr:Lys ratios of 53, 58, 63, 68, 73, and 78%. Diets with the lowest and highest Thr:Lys ratios were blended to achieve the target SID Thr:Lys treatments. The same set of pigs was used for the early and late trials and between experiments, all pens of pigs were fed a common diet for 28 d. In exp. 1, ADG and final BW increased (quadratic, P ≤ 0.025) with increasing SID Thr:Lys ratio with little improvement beyond the 63% SID Thr:Lys. Increasing Thr:Lys ratio improved (quadratic, P = 0.041) F/G ratio, appearing to have little improvement beyond 58% SID Thr:Lys. The quadratic polynomial (QP) model suggested that ADG was maximized at 69.0% SID Thr:Lys, while a similar fitting broken-line linear (BLL) model predicted no further improvement beyond 60.9%. For F/G, the QP model suggested minimum F/G was achieved at 74.3% SID Thr:Lys, while similar fitting BLL and BLQ models predicted no further improvement to F/G beyond 55.3 and 63.9%, respectively. In exp. 2, final BW tended to increase (quadratic, P = 0.061) with increasing SID Thr:Lys ratio and ADG increased (linear, P = 0.035; quadratic, P = 0.063), with the greatest numeric response between 63 and 68% SID Thr:Lys. Increasing SID Thr:Lys ratio improved (quadratic, P = 0.048) F/G up to 58 to 68% SID Thr:Lys ratio. Additionally, serum urea N decreased (linear, P = 0.016) with increasing SID Thr:Lys ratio. The QP model suggested that ADG was maximized at 70.3% SID Thr:Lys, while a similar fitting BLL model predicted no further improvement to ADG beyond 61.2%. For F/G, the QP model suggested minimum F/G was achieved at 68.7% SID Thr:Lys, while a similar fitting BLL model predicted no further improvement to F/G beyond 57%, respectively. In conclusion, the statistical models predict a wide range of SID Thr:Lys ratios to establish a requirement estimate for the different response criteria. However, for 82 to 154 lb pigs, there was little improvement in growth performance beyond a Thr:Lys ratio of 63%. For 212 to 265 lb pigs, the requirement estimate appeared to be between 63 and 68% Thr:Lys ratio. These results would suggest a similar requirement compared to our previous work in a commercial setting, based on SID Thr intake/d and SID Thr intake/kg of gain (Royall et al., 2023).
Keywords: amino acid; finishing pig; threonine; requirement